The Strategic Role and Institutional Function of the Zakat and Alms Hall in Islamic Daʿwah Propagation: A Case Study of BAZAS West Java - Suherdiana, Dadan; Zulkarnain, Andra; Kholifiah, Eli Melani; Karniati, Neng Nia (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze the role and function of Bale Zakat Sedekah (BAZAS) West Java in spreading da'wah through the management of zakat, infaq, and sedekah as a socio-religious instrument. The research method uses a qualitative approach, with data collected through interviews, observations, and documentation, to obtain a comprehensive picture of the institution's implementation of da'wah and empowerment. The results show that BAZAS has a strategic role in distributing Islamic philanthropic funds in a structured manner, both in economic, social, and da'wah aspects. From an economic perspective, zakat management can improve the welfare of mustahiq through empowerment programs that encourage financial independence. From a social aspect, this institution contributes to strengthening solidarity and welfare equality through the distribution of aid to groups in need. Meanwhile, in the context of da'wah, zakat distribution activities become a medium for da'wah bil-hal that presents Islamic values through concrete actions, not just verbal lectures. Thus, BAZAS functions as a transformative da'wah institution that positions zakat not only as ritual worship, but also a means of empowering the community in the modern era. However, optimizing the role of institutions still requires strengthening governance, transparency, and program evaluation to maximize the measurable impact of da'wah and empowerment. This research is expected to serve as a reference for developing an adaptive, productive, and sustainable zakat institutional model based on da'wah.